2002
DOI: 10.1097/00000539-200206000-00033
|View full text |Cite
|
Sign up to set email alerts
|

Ondansetron Inhibits the Analgesic Effects of Tramadol: A Possible 5-HT3 Spinal Receptor Involvement in Acute Pain in Humans

Abstract: Serotonin is an important neurotransmitter of the descending pathways that down-modulate spinal nociception. In postoperative pain, ondansetron, a selective 5-HT(3) receptor antagonist, increased the analgesic dose of tramadol. We suggest that, when antagonized for antiemetic purpose, 5-HT(3) receptors foster nociception, because of their site-dependent action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 16 publications
0
21
0
1
Order By: Relevance
“…The role that 5-HT 3 receptors play in regard to pain is controversial. Reports have stated that these receptors are not involved in the thermal pain inhibition produced by tramadol [20], whereas it was observed that in humans ondansetron inhibited tramadol's analgesic effect in postoperative pain [38]. On the other hand, Dogrul et al report that the spinal 5-HT 3 receptor participates in the antiallodynic and antihyperalgesic effect of tramadol, whereas the 5-HT 7 receptors participate in the antinociceptive effect [19].…”
Section: Discussionmentioning
confidence: 99%
“…The role that 5-HT 3 receptors play in regard to pain is controversial. Reports have stated that these receptors are not involved in the thermal pain inhibition produced by tramadol [20], whereas it was observed that in humans ondansetron inhibited tramadol's analgesic effect in postoperative pain [38]. On the other hand, Dogrul et al report that the spinal 5-HT 3 receptor participates in the antiallodynic and antihyperalgesic effect of tramadol, whereas the 5-HT 7 receptors participate in the antinociceptive effect [19].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the antinociceptive effect of tramadol was significantly diminished in 5-HT-lesioned mice. Previous data suggested that the descending serotonergic pathways and spinal 5-HT receptors play a crucial role in the antinociceptive and antihyperalgesic effects of tramadol [38,39]. On the other hand, another recent study observed that the intrathecal injection of minocycline significantly attenuated mechanical allodynia in a rat SNL model [40].…”
Section: Discussionmentioning
confidence: 99%
“…Ondansetron, a serotonin 5-HT3 receptor antagonist, α7 nAChR antagonist and antiemetic, produced significant decreases in alcohol consumption in early onset alcohol-dependent individuals compared to late-onset alcoholics in an open-label 8-week study (Arcioni et al, 2002; Kranzler et al, 2003). These findings were consistent with others who found that ondansetron dose-dependently promoted abstinence in early-onset patients, but not in late-onset patients (Roache et al, 2008).…”
Section: Need: a Better Understanding Of The Co-morbid Conditionmentioning
confidence: 99%